Contrast induced hyperthyroidism due to iodine excess - Mushtaq, Usman (BMJ Publishing Group, 2009)
Iodine induced hyperthyroidism is a thyrotoxic condition caused by exposure to excessive iodine. Historically this type of hyperthyroidism has been described in areas of iodine deficiency. With advances in medicine, iodine induced hyperthyroidism has been observed following the use of drugs containing iodine—for example, amiodarone, and contrast agents used in radiological imaging. In elderly patients it is frequently difficult to diagnose and control contrast related hyperthyroidism, as most of these patients do not always present with typical signs and symptoms of hyperthyroidism. Treatment can be very challenging as drugs commonly used to treat hyperthyroidism have little effect on already formed thyroid hormone due to iodine excess.